Rene Girard and the phenomenology of mimetic desire - Gregory Moss (Studia z Teorii Wychowania)
René Girard has been critiqued for failing to ground his theory of mimetic desire in a discursive and philosophically robust framework. In order to meet this objection, I argue that René Girard’s theory of mimetic desire can be successfully motivated by a phenomenology of the emptiness of selfhood and intersubjectivity. After grounding Girard’s theory in a phenomenology of no-self, I reconstruct Girard’s argument that violence is a necessary consequence of internally mediated mimetic desire